Peri‐operative COVID‐19 infection in urgent elective surgery during a pandemic surge period: a retrospective observational cohort study. (22nd October 2020) - Kane, A. D.; Paterson, J.; Pokhrel, S.; Berry, S. K.; Monkhouse, D.; Brand, J. W.; Ingram, M.; Danjoux, G. R.
Summary: Maintaining safe elective surgical activity during the global coronavirus disease 2019 (COVID‐19) pandemic is challenging and it is not clear how COVID‐19 may impact peri‐operative morbidity and mortality in this population. Therefore, adaptations to normal care pathways are required. Here, we establish if implementation of a bespoke peri‐operative care bundle for urgent elective surgery during a pandemic surge period can deliver a low COVID‐19‐associated complication profile. We present a single‐centre retrospective cohort study from a tertiary care hospital of patients planned for urgent elective surgery during the initial COVID‐19 surge in the UK between 29 March and 12 June 2020. Patients asymptomatic for COVID‐19 were screened by oronasal swab and chest imaging (chest X‐ray or computed tomography if aged ≥ 18 years), proceeding to surgery if negative. COVID‐19 positive patients at screening were delayed. Postoperatively, patients transitioning to COVID‐19 positive status by reverse transcriptase polymerase chain reaction testing were identified by an in‐house tracking system and monitored for complications and death within 30 days of surgery. Out of 557 patients referred for surgery (230 (41.3%) women; median (IQR [range]) age 61 (48–72 [1–89])), 535 patients (96%) had COVID‐19 screening, of which 13 were positive (2.4%, 95%CI 1.4–4.1%). Out of 512 patients subsequently undergoing surgery, 7 (1.4%) developed COVID‐19 positive status (1.4%, 95%CI 0.7–2.8%) with one COVID‐19‐related death (0.2%, 95%CI 0.0–1.1%) within 30 days. Out of these seven patients, four developed pneumonia, of which two required invasive ventilation including one patient with acute respiratory distress syndrome. Low rates of COVID‐19 infection and mortality in the elective surgical population can be achieved within a targeted care bundle. This should provide reassurance that elective surgery can continue, where possible, despite high community rates of COVID‐19.